Magnetic resonance cholangiopancreatography: utilization and usefulness in suspected choledocholithiasis. Issue 12 (29th September 2014) - Toppi, Jason T.; Johnson, Mary Ann; Page, Patrick; Fox, Adrian
Abstract: Background: The aim of this study was to evaluate the role of magnetic resonance cholangiopancreatography in cases of suspected choledocholithiasis. Methods: Suitable candidates were recruited from a database of all consecutive patients who underwent magnetic resonance cholangiopancreatography between March 2009 and December 2012. Patients were stratified into low, medium and high risk for choledocholithiasis by assessing clinical symptoms, liver function tests and ultrasonography. True negatives and false positives were calculated based on endoscopic retrograde cholangiopancreatography, intraoperative cholangiogram and clinical follow‐up. Results: Of 201 magnetic resonance cholangiopancreatography investigations conducted, choledocholithiasis was diagnosed in 37 (18%) patients. In total, there was one false negative and three false positives. Total sensitivity and specificity values were 97% and 98%, respectively. These values were highest among low‐risk patients (100% for both sensitivity and specificity). By initially opting for magnetic resonance imaging in suitable moderate‐ and high‐risk patients, unnecessary endoscopic retrograde cholangiopancreatography procedures were avoided in 61% and 65% of patients, respectively. Conclusion: Magnetic resonance cholangiopancreatography for patients with suspected choledocholithiasis yields high sensitivity and specificity. Given its reduced risk profile and relative ease of administration, magnetic resonance cholangiopancreatography is a necessary tool for the assessment of choledocholithiasis with the capacity to rival gold standard diagnostic techniques and help reduce the number of unnecessary interventional procedures.